2013
DOI: 10.1002/jclp.21959
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Shame on the Therapeutic Alliance and Intimate Relationships

Abstract: These findings have implications for the theoretical role of shame in mental health presentations as well as the potential for internalizing shame coping styles (i.e., withdrawal, attack self) to act as a barrier to successful therapy and interpersonal relationships. The inclusion of shame-focused assessments and interventions in the initial stages of treatment with clients exhibiting these strategies could improve prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 20 publications
4
42
0
Order By: Relevance
“…Currently, new models of treatment for childhood sexual abuse and complex trauma (e.g., STAIR Narrative Therapy; Cloitre et al, 2014) incorporate emotional regulation strategies and coping skills in the initial phases of therapy to provide a stable base for clients to then engage in later trauma processing. Bearing in mind the unhelpful role of some shame coping styles observed in the current study and recent findings that shame responding can be a barrier to the therapeutic alliance (Black et al, 2013), the integration of shame interventions at these early therapeutic stages would be beneficial.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Currently, new models of treatment for childhood sexual abuse and complex trauma (e.g., STAIR Narrative Therapy; Cloitre et al, 2014) incorporate emotional regulation strategies and coping skills in the initial phases of therapy to provide a stable base for clients to then engage in later trauma processing. Bearing in mind the unhelpful role of some shame coping styles observed in the current study and recent findings that shame responding can be a barrier to the therapeutic alliance (Black et al, 2013), the integration of shame interventions at these early therapeutic stages would be beneficial.…”
Section: Discussionmentioning
confidence: 74%
“…Ironically, "withdrawal" was initially asserted as a psychologically healthy shame coping style (see Nathanson, 1992). Gathering empirical evidence has provided a different picture of this coping style and found that it is both a problematic coping strategy for DID and a risk factor for difficulties in both forming effective therapeutic relationships and overall relationship functioning (Black et al, 2013;Dorahy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They did not find any significant relationship between self-shame and coping mechanisms; however, they found a significant correlation between shame coping style and PTSD, and said, "In PTSD samples, a specific, definable trauma, or multiple traumas (e.g., childhood abuse, rape), can clearly be linked to the emergence of shame-related coping; however, the nature and origins of shame coping styles in non-trauma groups is less clear" (p. 646). In short, the definition of shame is very subjective, and it might differ based on a client's self-concept (Black et al, 2013;Harder & Lewis, 1987;Tangney & Dearing, 2002). Thus, researchers would more carefully define shame because it might be different in diverse social and cultural contexts.…”
Section: Shame Guilt and Hopementioning
confidence: 99%
“…From this rationale, attachment pattern, cognitive-emotional factors (e.g., alexithymia), and the dominant behavioural coping strategies of clients could be highly salient factors in the therapeutic alliance of clients with PTSD (Ackerman & Hilsenroth, 2003;Black, Curran, & Dyer, 2013).…”
Section: Ptsd/trauma Have Been Experienced Over the Past 35 Years In mentioning
confidence: 99%